2020
DOI: 10.1021/acs.langmuir.9b03459
|View full text |Cite
|
Sign up to set email alerts
|

Buckling Effect of Sole Zeolitic Imidazolate Framework-8 Nanoparticles Adsorbed at the Water/Oil Interface

Abstract: The buckling phenomenon of sole zeolitic imidazolate framework-8 (ZIF-8) particles adsorbed at the water/oil interface was systematically studied. The droplet of ZIF-8 water dispersion was pended in oil for a certain time period and manually extracted to decrease the volume. With the reduction of interfacial area, the ZIF-8 particles were jammed together to form a wrinkling solid film at the water/oil interface, which could withstand the extraction of the droplet and be regenerated. The size and concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…ZIF‐8 particles with micron size were prepared according to the reported literature with some minor modifications. [ 29,30 ] Scanning electron microscopy (SEM) revealed that the obtained particles were rhombic dodecahedral in shape with an average size of 1.8 µm (Figure S1, Supporting Information). Powder X‐ray diffraction (XRD) further confirmed the crystal structure of ZIF‐8, showing the same diffraction peaks as the simulated pattern (Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ZIF‐8 particles with micron size were prepared according to the reported literature with some minor modifications. [ 29,30 ] Scanning electron microscopy (SEM) revealed that the obtained particles were rhombic dodecahedral in shape with an average size of 1.8 µm (Figure S1, Supporting Information). Powder X‐ray diffraction (XRD) further confirmed the crystal structure of ZIF‐8, showing the same diffraction peaks as the simulated pattern (Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…ZIF‐8 was synthesized according to the literature with some minor modifications. [ 29,30 ] Typically, 8.11 g 1‐methylimidazole and 8.11 g 2‐methylimidazole were dissolved in 500 mL methanol. 7.34 g Zn(NO 3 ) 2 ⋅6H 2 O was dissolved in 500 mL methanol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome the limitation, the oil–water interfacial area could be increased by forming oil-in-water (O/W) or water-in-oil (W/O) emulsions using surfactants/particles. The particle-stabilized emulsions, so-called Pickering emulsions, , have been shown to be excellent platforms for interfacial reactions, a process named Pickering interfacial catalysis (PIC). , Because of the protection by the particle layer, dissolved enzymes in the aqueous phase are less exposed to the organic phase, reducing the possibility of their deactivation by the organic phase . However, the catalysis efficiency of free enzymes in Pickering emulsion systems is still restricted by diffusional limitations, resulting from the diffusing time the enzymes spend on locating close to the oil–water interface …”
Section: Introductionmentioning
confidence: 99%
“…Emulsions play an important role in a wide range of chemical and industrial fields, such as oil industry, food engineering, , pharmaceuticals, and cosmetics . Emulsions are usually formed by mixing two or more immiscible liquids (e.g., oil and water) with interfacially active materials, such as surfactants, asphaltenes, , and nano/microparticles. The emulsions stabilized with particles are commonly called Pickering emulsions, which have been studied for more than a century following Pickering’s pioneering work in 1907 . It is generally accepted that the particles with partial wettability in both aqueous and organic phases can adsorb to the oil/water interface.…”
Section: Introductionmentioning
confidence: 99%